2012
DOI: 10.1073/pnas.1108517109
|View full text |Cite
|
Sign up to set email alerts
|

Chimpanzees’ flexible targeted helping based on an understanding of conspecifics’ goals

Abstract: Humans extensively help others altruistically, which plays an important role in maintaining cooperative societies. Although some nonhuman animals are also capable of helping others altruistically, humans are considered unique in our voluntary helping and our variety of helping behaviors. Many still believe that this is because only humans can understand others’ goals due to our unique “theory of mind” abilities, especially shared intentionality. However, we know little of the cognitive mechanisms underlying he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
166
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(184 citation statements)
references
References 32 publications
15
166
3
Order By: Relevance
“…Such behaviours can make some acts of intentional communication more easily interpretable than others, by providing rich evidence for a speaker's communicative intentions (Moore, 2013b). Additionally, Sperber and Wilson (1995;2002) propose the existence of a cognitive module, unique to humans, that processes food, they respond appropriately to requests produced using an ambiguous begging gesture (Yamamoto et al, 2012). This suggests that they can, in at least limited contexts, make inferences about an interlocutor's communicative goal.…”
Section: Iii(b) the Complex Inferences Objectionmentioning
confidence: 99%
“…Such behaviours can make some acts of intentional communication more easily interpretable than others, by providing rich evidence for a speaker's communicative intentions (Moore, 2013b). Additionally, Sperber and Wilson (1995;2002) propose the existence of a cognitive module, unique to humans, that processes food, they respond appropriately to requests produced using an ambiguous begging gesture (Yamamoto et al, 2012). This suggests that they can, in at least limited contexts, make inferences about an interlocutor's communicative goal.…”
Section: Iii(b) the Complex Inferences Objectionmentioning
confidence: 99%
“…Moreover, Melis and colleagues (2011) found that chimpanzees will also release a hook to send food down a ramp to a desirous conspecific, if it is clear that they cannot get the food themselves and if the recipient actively signals his need. Finally, Yamamoto and colleagues (2009) observed chimpanzees giving tools to others that needed to rake in food for themselves, and more recently showed that chimpanzees demonstrate flexible "targeted" helping, i.e., giving the specific tool that the conspecific needs from an array of possible tools (Yamamoto et al 2012).…”
Section: Cooperation In Great Ape Societiesmentioning
confidence: 99%
“…The main mechanism for human prosociality is assumed to be empathy (4), which has been hypothesized to extend to all mammals (5). After a period during which there was a lack of evidence for nonhuman primate prosociality, including claims of human uniqueness in this regard (6,7), carefully controlled experiments have demonstrated well developed prosocial tendencies in monkeys (8)(9)(10) and apes (11)(12)(13)(14). The ecological validity of experimental findings on prosociality is supported by the many naturalistic observations of the same tendencies expressed spontaneously among chimpanzees and other nonhuman primates (3,15,16).…”
mentioning
confidence: 99%